Revenue Diversification and Financial Independence in Higher Education through an Analysis of the Australian National University’s Funding Structure - Naya Arifah Syihab; Mustajib (Center for Studies in Advanced Science, 2026)
A sustainable and diversified revenue structure is essential for higher education institutions to maintain financial stability amid changing funding environments. However, many universities, including the Australian National University (ANU), still face challenges related to dependence on government funding. This study aims to analyze the revenue structure of ANU during the 2022–2023 fiscal years and examine its shift toward financial diversification. This research employs a descriptive quantitative design using common size analysis to evaluate the proportion of each revenue component based on ANU’s official financial reports. The data were analyzed to identify changes in revenue composition and trends across the two fiscal years. The findings indicate that although government funding remains the dominant source of revenue, its proportional contribution has declined, while non-government income particularly from other income sources has increased significantly. This shift reflects a gradual movement toward a more diversified revenue structure. The study contributes to the literature on higher education financial management by providing empirical evidence of revenue diversification in a world-class university context and offers practical insights for developing sustainable and balanced funding strategies